Acquired auricular cauliflower deformity in a child. - Diaconeasa, A.; Chiriac, A.; Wollina, U. (European Journal of Pediatric Dermatology, 2025)
Cauliflower ears are a permanent deformation of the auricle after blunt or cutting trauma with hematoma. The disease is a consequence of inflammation and fibrocartilaginous growth. It is rare among infants and children. We present the case of a 7-year-old boy with bilateral auricular deformation. After exclusion of other possible causes, the diagnosis of cauliflower ears type IA was confirmed. The parents were advised to prevent trauma. Surgical correction was not accepted.